Safety Risk Analysis of Cliff Landslide Handling Using The Hirarc (Hazard Identification, Risk Assessment, And Risk Control) to Reduce The Frequency of Mine Operational Incidents at PT Semen Gresik - Syaifuddin, M.; Primasanti, Yunita; Indriastiningsih, Erna (Institut Teknologi Bisnis AAS Indonesia, 2025)
Work safety is a crucial aspect of the Cement industry, especially in high-risk jobs such as handling cliff landslides. This study aims identify potential hazards, assess risks, and control them using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method to reduce the frequency of operational incidents at PT Semen Gresik. The research employs field observations, interviews with workers, and data analysis using the HIRARC approach. Findings indicate that before implementing this method, several tasks were categorized as high risk and extreme risk. After risk control measures were applied, the level of risk was reduced to moderate risk and low risk. This study recommends changing the slope design from single slope to multi slope, which has been proven to increase the Safety Factor (SF) to 1.742. Additionally, improving work safety management is suggested through the promotion of Occupational Safety and Health (K3) and the installation of Extenso Meters to monitor ground movement.